Investigating Human Neurovascular Coupling Using Functional Neuroimaging: A Critical Review of Dynamic Models - Huneau, Clément; Benali, Habib; Chabriat, Hugues (Frontiers in Neuroscience, 2015)
The mechanisms that link a transient neural activity to the corresponding increase of cerebral blood flow (CBF) are termed neurovascular coupling (NVC). They are possibly impaired at early stage of small vessel or neurodegenerative diseases. Investigation of NVC in human has been made possible since the development of various neuroimaging techniques based on variations of local hemodynamics during neural activity. Specific dynamic models are currently used for interpreting these data that can include biophysical parameters related to NVC. We reviewed the seven models with explicit integration of NVC found in the literature and described their physiological assumption, mathematical formalism and validation. All models were described regarding a constant schematic formalism. Differences between them, particularly regarding their complexity, and hence, their potential use were finally evaluated. These models may provide key information to investigate various aspects of NVC in human pathology.